Evaporation, from exoplanets to exocomets - Lecavelier des Etangs, Alain (Comptes Rendus. Physique, 2023)
Here we review the last advances in our understanding of exoplanetary upper atmospheres, with a focus on the evaporation of exoplanets orbiting close to their stars. The atmospheric escape takes a significant part on the phenomena that sculpt the population of planets with short orbital distances.We also observe evaporation of minor bodies in young planetary systems when they approach to their star. These “exocomets” have been studied since the mid 80’s, yielding a large amount of observational data. In particular, in the case of exocomets orbiting the young star β Pictoris, it has been shown that there are two different families of comets, tracing two different dynamical histories. Most recently, photometric observations with the NASA TESS space observatory allowed the detection of the dust tails produced by the evaporation of the exocomets’ nuclei. Using numerical simulation these observations allowed the derivation of the comets nuclei size distribution, which is found to be strikingly similar to the one observed in the Solar system and to the one expected for a collisionally relaxed population of minor bodies.